2003
DOI: 10.1093/jnci/95.14.1062
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Type 16 and Immune Status in Human Immunodeficiency Virus-Seropositive Women

Abstract: The prevalent and incident detection of HPV16 is more weakly associated with immune status in HIV-seropositive women than that of other HPV types, suggesting that HPV16 may be better at avoiding the effects of immune surveillance, which could contribute to HPV16's strong association with cervical cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
173
5
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(209 citation statements)
references
References 28 publications
25
173
5
6
Order By: Relevance
“…In particular, a meta-analysis of studies from around the world found that HPV 16 was significantly less prevalent in high grade squamous intraepithelial lesions (HSILs) from HIVseropositive women than in the general female population, 2 and two large, independent cohorts found that the prevalence of HPV 16 was more weakly associated with CD41 T-cell count than the prevalence of any other HPV type. 3 HPV 16's relative independence from immune status in these studies has been interpreted as evidence that HPV 16 may be innately better than other HPV types at avoiding the effects of immune surveillance and, thereby, less affected by changes in immune status.…”
Section: Dear Sirmentioning
confidence: 83%
“…In particular, a meta-analysis of studies from around the world found that HPV 16 was significantly less prevalent in high grade squamous intraepithelial lesions (HSILs) from HIVseropositive women than in the general female population, 2 and two large, independent cohorts found that the prevalence of HPV 16 was more weakly associated with CD41 T-cell count than the prevalence of any other HPV type. 3 HPV 16's relative independence from immune status in these studies has been interpreted as evidence that HPV 16 may be innately better than other HPV types at avoiding the effects of immune surveillance and, thereby, less affected by changes in immune status.…”
Section: Dear Sirmentioning
confidence: 83%
“…8,9 This data is also consistent with prior longitudinal studies that attributed the elevated prevalence of cervical HPV infection among HIV-infected women to both an increased risk of incident and persistent infection as severity of immunosuppression increased. 10,[18][19][20][21][22][23][24][25] Strickler and colleagues recently reported a strong interaction between serum HIV viral load and CD4 cell count on cervical HPV natural history in the WIHS study cohort. 24 Because of sample size constraints, a larger study will be needed to evaluate the interaction of HIV viral load and CD4 cell count on oral HPV natural history.…”
Section: Discussionmentioning
confidence: 99%
“…All subjects provided informed consent and each local institutional review board provided approval for the study. On an ongoing basis, the Women's Interagency HIV Study conducts semiannual study visits during which serum is obtained, and a cervicovaginal lavage specimen is collected for HPV DNA testing followed by a Papanicolaou smear (12)(13)(14). All Papanicolaou smears were interpreted centrally using the 1991 Bethesda System criteria (15).…”
Section: Methodsmentioning
confidence: 99%